Laser Fabrication and Comparative Study of Planoconcave and Planoconvex Microlenses on Fused Silica and Sapphire - Narayana R. Gottumukkala; Caleb Barnes; Mool C. Gupta (Micromachines)
We report on fabricating planoconcave lenses using a picosecond 355 nm wavelength laser and a CO2 laser. We also report the fabrication of the planoconvex microlens array on fused silica by patterned micromachining using a picosecond laser and reshaping using a CO2 laser. We report results on the surface morphology, profile, roughness, optical transmission efficiency, and laser beam profile of transmitted light passing through the microlens. We demonstrate laser fabrication of planoconcave lenses on infrared transmitting material sapphire. Furthermore, we present the results of an experimental and simulation comparative performance study of planoconcave microlenses obtained by individual picosecond and CO2 lasers.